PENDAMPINGAN PENYUSUNAN KURIKULUM MERDEKA DI RAUDHATUL ATHFAL MIFTAHUL ULUM KECAMATAN MRANGGEN DEMAK - Sagala, Anita Chandra Dewi; Mila Karmila; Ratna Wahyu Pusari (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
In Mranggen District, especially in Ngemplak and RA Miftahul Ulum Districts, RA teachers do not yet have the ability to develop independent curriculum teaching tools. Teachers' knowledge regarding the preparation of learning tools is very important to provide and drill into. Preparing learning curriculum tools is important, where almost all schools under the Ministry of Education and Culture have socialized the independent curriculum and implemented the independent curriculu m in learning at PAUD. The solution offered is training and assistance in preparing independent curriculum tools starting from teaching modules, projects to strengthen the Pancasila profile (P5) and learning assessments. It is hoped that the implementation of the independent curriculum training will make it easier for teachers in RA Mranggen District to prepare open tools. The results of the service in Mranggen District show that RA teachers are very enthusiastic in studying the implementation of the Merdeka curriculum to be put into practice in their respective schools.